Effect of intraoperative anaesthetic management on patients' pain scores in post-anaesthesia care unit after caesarean section - Samina Ismail; Asiyah Aman; Alia Hussain (Wolters Kluwer Medknow Publications, 2018)
Objective: To determine the effect of intraoperative factors while using technique of anaesthesia and use of specific opioids on patients' pain score and need for first rescue analgesia in the post-anaesthesia care unit (PACU) after caesarean section (CS).Patients and Methods: This is a cross-sectional study on CS patients with 6 months collected data that include patients' demographics, surgical incision, duration of surgery, technique of anaesthesia, intraoperative use of specific opioids/co-analgesia, numerical rating score (NRS) and time of first rescue analgesia in the PACU.Results: Among 334 patients enrolled in the study, 7.2-13.3% had NRS >4 and required first rescue analgesia within the first hour in the PACU with 28 (8.4%) patients at time zero and 20 (6.0%) patients at 30 min in the PACU. There was no statistically significant difference among patients having NRS >4 from those having ≤4 in terms of the type of incision, American Society of Anaesthesiologist grading and duration of surgery. A statistically significant (P-value < 0.01) low pain scores in the initial 30 min in the PACU was observed in patients having surgery under regional anaesthesia (RA) compared to general anaesthesia (GA) and in patients receiving intraoperative intravenous (IV) morphine compared to nalbuphine or tramadol when operated under GA.Conclusion: The need for rescue analgesia during the initial 30 min in the PACU was less in patients undergoing CS under RA or receiving IV morphine under GA.